Updated management of differentiated thyroid carcinoma - Akter, Farhana (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Differentiated thyroid cancer (DTC) is the most common type of thyroid cancer and one of the most frequently diagnosed endocrine cancers. The American Thyroid Association (ATA) initially published guidelines for DTC management in 1996, with subsequent revisions reflecting advancements in the field. The most recent update aims to provide clinicians, patients, researchers, and policymakers with comprehensive, evidence-based recommendations for managing adult DTC patients, emphasizing the patient’s journey from diagnosis through treatment and long-term care. The updated guidelines were developed by a diverse panel of experts, including specialists in thyroid cancer care, a patient advocate, and experts in systematic reviews and guidelines. Systematic literature reviews were conducted, and two additional reviews were commissioned, with evidence drawn from English-language articles published up until July 1, 2024. The Grading of Recommendations Assessment, Development and Evaluation system was used to assess the quality of the evidence. The revised guidelines cover various aspects of DTC management, starting with diagnosis and extending to staging, treatment, response assessment, monitoring strategies, diagnostic testing, and subsequent therapies. Emphasis is placed on patient-reported outcomes and areas identified for further research. By incorporating the latest evidence, the guidelines aim to optimize clinical decision-making and improve patient care throughout their treatment journey. This presentation will highlight the key aspects of these updated guidelines, providing an overview of the current standards in DTC management. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S8]